Challenges and opportunities for hybrid rice in Bangladesh - Spielman, David J.; Ward, Patrick S.; Kolady, Deepthi Elizabeth; Ar-Rashid, Harun (University Press Limited, 2021)
Many studies suggest that hybrid rice can contribute to food security in developing countries, especially in parts of Asia where rice production is so vital to the rural economy and where rice remains a staple of both urban and rural food consumption. The higher yields attributable to hybrid rice have the potential to increase food availability for farm households’ own consumption, while also increasing farm incomes through sales of larger marketable surpluses. These larger marketable surpluses can result in increased food supplies that reduce or stabilize prices for both urban and rural food-insecure households (see e.g. Lin and Pingali 1994; Xie and Hardy 2009).